Influence of Coatings on Postharvest Physiology and Shelf life of Kinnow Fruits under Super Market Conditions - Mahajan , B V C; Singh , Rupinder (Journal of Postharvest Technology, 2014)
The Kinnow mandarin (Citrus nobilis x Citrus deliciosa) fruits after harvesting  were coated with different coating emulsions viz. cellulose, citrashine,  terpenoidal oligomer and sta-fresh. The control fruits were kept uncoated. The  fruits were stored under supermarket conditions (18-20°C and 80-85% RH).  The observations on various physico-chemical attributes of fruits were  recorded at different storage intervals. The data revealed that fruits coated with  citrashine or terpenoidal oligomer coatings can be stored for 15 days under  supermarket conditions (18-20°C and 80-85% RH) with highly acceptable  quality as compared to control which maintained storage life of one week only.
Keywords: Kinnow; Coatings; Physiological changes Storage